Exonerations in the United States, 1989-2012: Report by the National Registry of Exonerations - Gross, Samuel R. (2012)
This report is about 873 exonerations in the United States, from January 1989 through February 2012. Behind each is a story, and almost all are tragedies. The tragedies are not limited to the exonerated defendants themselves, or to their families and friends. In most cases they were convicted of vicious crimes in which other innocent victims were killed or brutalized. Many of the victims who survived were traumatized all over again, years later, when they learned that the criminal who had attacked them had not been caught and punished after all, and that they themselves may have played a role in condemning an innocent person. In many cases, the real criminals went on to rape or kill other victims, while the innocent defendants remained in prison. Some of the stories have villains; many do not. Few have happy endings